Improving social forestry in Indonesia - Recommendations for CSOs - Santoso, H.; Purwanto, E. (2020)
As part of a multi-country review of community forest rights, Tropenbos Indonesia conducted a review of Indonesia’s social forestry programme, aiming to assess its environmental and livelihood outcomes, and identify ways to improve these outcomes and the role that Civil Society Organisations (CSOs) can play in this. In this policy brief we summarize some of the main outcomes of the review, and the consequent recommendations for CSOs.